A Numerical Investigation of the Influence of the Material Microstructure on the Failure Mode of Metal Ceramic Composites - PANDI, Pitchai; BOLZON, Gabriella (Engineering Transactions, 2016)
Metal failure is often initiated by strain localization in narrow bands. In metal matrix composites, the occurrence and the consequences of this phenomenon are influenced by the material microstructure. This dependency has been numerically investigated by considering periodic and quasi-periodic arrangement of ceramic fibers in a metal matrix, with reinforcement content varying between 10% and 50% in volume. The constitutive response of the metal has been simulated by the widely used GTN (Gurson-Tvergaard-Needleman) continuum damage-plasticity model with evolution law based on local porosity. The onset of failure for the composite has been identified with the critical growth of micro voids that induce softening at the macro scale. An extensive study has been performed in order to distinguish the effects of the material microstructure, the role of the imperfections and the influence of the simulation details. The main results of this investigation are summarized in this paper.